Comparison of Traditional Chinese Medicine and Traditional Iranian Medicine in Diagnostic Aspect - Shadi Sarebanha; AmirHooman Kazemi; Paymon Sadrolsadat; Niu Xin (Tehran University of Medical Sciences, 2016)
Iranian traditional medicine (TIM) has a long and old history from ancient periods up to now and it  is  used  in  prevention,  diagnosis,  treatment,  and  elimination  of  diseases  in  Persia  and neighboring countries. In Traditional Iranian Medicine,  physiological functions of the human body are based on 7 factors: Elements, Temperament, Humors, Organs, Spirits, Forces or Faculty, Functions. Traditional Chinese Medicine (TCM) with 3000-5000 year of history has a unique system to  diagnosis  and  prevention  of  diseases.  TCM with acupuncture  and  Chinese  herbal medicine is one of the most important parts in complementary and alternative medicine. The clinical diagnosis and treatment in TCM are mainly based on the yin-yang and five elements theories. The aim of present study is to assess differences of TCM and TIM in diagnostic aspect for this purpose we searched Iranian databases and 30 years review articles of the Chinese scholar database (CNKI, VIP...) and relevant articles published in Journals inside and outside of China without language restrictions. The results showed that diagnosis in TIM is mostly focused on urine analysis, smelling, and pulse-taking, while a diagnosis of diseases in TCM is mainly focused on tongue observation and pulse taking. It seems that through the time some parts of diagnosis are missed. If practitioners take advantages from traditional medicine and combine it with the science of western medicine, it could be a great help for integrative medicine. Our knowledge about each of the traditional medicine not only should not be against the other types of traditional medicine but also it should be a help for finding information about missed parts.